2016
DOI: 10.1189/jlb.2a0515-197r
|View full text |Cite
|
Sign up to set email alerts
|

TLR4, TLR7/8 agonist-induced miR-146a promotes macrophage tolerance to MyD88-dependent TLR agonists

Abstract: TLRs facilitate the recognition of pathogens by immune cells and the initiation of the immune response, leading to the production of proinflammatory cytokines and chemokines. Production of proinflammatory mediators by innate immune cells, such as macrophages, is tightly regulated to facilitate pathogen clearance while limiting an adverse impact on host tissue. Exposure of innate immune cells to TLR ligands induces a state of temporary refractoriness to a subsequent exposure of a TLR ligand, a phenomenon referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…These two miRNAs are significantly down-regulated in female EV miRNAs. Published literature also confirms some of these target genes at mRNA and functional levels (using luciferase assay) 39, 6365 .…”
Section: Discussionmentioning
confidence: 71%
“…These two miRNAs are significantly down-regulated in female EV miRNAs. Published literature also confirms some of these target genes at mRNA and functional levels (using luciferase assay) 39, 6365 .…”
Section: Discussionmentioning
confidence: 71%
“…TLRs play a central role in the recognition and response to invading pathogens by immune cells, leading to the production of pro-inflammatory cytokines and chemokines (25). The TLR7/8, signaling pathway, which includes recruitment of MyD88, could be an important target for treating psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, overexpression of miR‐146a was adequate to mimic LPS or R848‐induced hypo‐responsiveness . Contrarily, inhibition of miR‐146a activity leads to LPS‐ or R848‐induced TLR hyper‐responsiveness in TLR signaling tolerance through modulation of MyD88 in human macrophages …”
Section: Role Of Mirnas In Pattern Recognition Receptors Signaling Anmentioning
confidence: 97%
“…Nahid et al. showed that TLR4 agonist (LPS) and TLR7/8 ligand (R848) induce homologous and heterologous tolerance in monocyte/macrophages, which leads to aberrant production of chemokines and cytokines . Functionally, overexpression of miR‐146a was adequate to mimic LPS or R848‐induced hypo‐responsiveness .…”
Section: Role Of Mirnas In Pattern Recognition Receptors Signaling Anmentioning
confidence: 99%
See 1 more Smart Citation